A checklist of Onagraceae in the Pan-Himalaya region - Luo, Yike; Xie, Lei (Phytotaxa, 2023)
This study provides a checklist of Onagraceae in the Pan-Himalayan region based on extensive specimen consultation, literature investigation, and field surveys. According to recent phylogenetic studies and taxonomic revisions, five genera of Onagraceae are recognized including a total of 56 species in the Pan-Himalayan region. The five genera are Chamaenerion, Circaea, Epilobium, Oenothera, and Ludwigia. In this checklist, we verified all the validly published names in this region and confirmed their taxonomic status. Type status of names are checked according to the International Code of Nomenclature for algae, fungi and plants (ICN). Epilobium ladakhianum is treated as a new synonym of E. williamsii and lectotypification of Chamaenerion conspersum is made, which are the taxonomic novelties in this study. In addition, we provide identification keys to all the genera and their species, descriptions of the five genera, and distribution ranges as well as taxonomic notes for the species.